3.5 Worked and modified shell (Scottish Archaeological Internet Reports, 2009)
A small assemblage of worked and decorative shell was found in the shell midden at Sand. it comprises scallop and cowrie shells and constitutes all the scallop and cowrie from Sand. In addition, a small assemblage of perforated limpet shells has been considered. it is not yet clear whether the limpet perforations are natural or artificial, but it is possible that the shells were deliberately collected.